2011
DOI: 10.1021/nl201351f
|View full text |Cite
|
Sign up to set email alerts
|

A High Quantum Efficiency Preserving Approach to Ligand Exchange on Lead Sulfide Quantum Dots and Interdot Resonant Energy Transfer

Abstract: We present a new approach to ligand exchange on lead sulfide (PbS) quantum dots (QDs) in which the QDs are reacted with preformed Pb cation-ligand exchange units designed to promote reactions that replace surface Pb and oleate groups on the as-grown QDs. This process introduces negligible surface defects as the high quantum efficiency (∼55%) of the as-grown QDs is maintained. Infrared spectroscopy and electron microscopy are used to confirm the replacement of ligands and time-resolved photoluminescence to demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 45 publications
3
65
0
3
Order By: Relevance
“…23 These experiments reveal that Förster theory correctly predicts scaling parameters that affect the energy transfer rate in QD solids. 15,16,19,22,26 To understand the dynamics of excitons in QD solids, let us consider a model QD solid system that is illustrated in Figure 1a. This model system includes QDs assembled in a two-dimensional hexagonally closed packed lattice.…”
Section: Model Of Energy Transfer In Quantum Dot Solidsmentioning
confidence: 99%
“…23 These experiments reveal that Förster theory correctly predicts scaling parameters that affect the energy transfer rate in QD solids. 15,16,19,22,26 To understand the dynamics of excitons in QD solids, let us consider a model QD solid system that is illustrated in Figure 1a. This model system includes QDs assembled in a two-dimensional hexagonally closed packed lattice.…”
Section: Model Of Energy Transfer In Quantum Dot Solidsmentioning
confidence: 99%
“…Engineering the surface of luminescent quantum dots (QDs) plays a significant role in altering their physicochemical properties such as emission characteristics, stability, and solubility, which in turn affects their utility in biological and optoelectronic applications 1–7. Various surface modifying strategies such as ion exchange, ligand exchange, and complexation have been reported to improve the optical performance of QDs in numerous applications, such as light‐emitting devices (LEDs), biological imaging, optical sensors, and other energy devices of QDs 1–7. For example, modification of the surface of QDs with a luminescent inorganic complex helped to fabricate an environmentally sustainable WLE composite that showed a perfect white light nature, which has applications in neurotransmitters and reversible pH sensing 5–7.…”
Section: Introductionmentioning
confidence: 99%
“…We surmised that these results could be due to desorption of Pb adatoms upon ligand stripping, as others have reported on the lability of excess surface Pb atoms under certain conditions. [18] Indeed, inductively coupled plasma atomic emission spectroscopy (ICP-AES) revealed that PbSe-OA nanocrystals stripped with Et 3 OBF 4 have a nearly equimolar ratio of Pb:Se (0.97:1.00), while the initial sample had the expected lead-rich ratio of 1.22:1.00.…”
mentioning
confidence: 99%